Countering religious extremism: the need for regional collaboration - Noor Huda Ismail (2024)
In this digital age, where information flows seamlessly across borders, the interplay between misinformation, disinformation, hate speeches, hoaxes, and violent extremism demands our attention. This intricate nexus is not just theoretical; it played a major role in the harrowing journeys of individuals like Rullie Rian Zeke and Ulfah Andayani Saleh and their children. Their story reflects the broader challenges facing our interconnected world and emphasises the critical need for regional collaboration in fighting transnational terrorism.